2016
DOI: 10.1074/jbc.m115.712745
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Astrin Regulates Its Kinetochore Function

Abstract: The error-free segregation of chromosomes, which requires the precisely timed search and capture of chromosomes by spindles during early mitotic and meiotic cell division, is responsible for genomic stability and is achieved by the spindle assembly checkpoint in the metaphase-anaphase transition. Mitotic kinases orchestrate M phase events, such as the reorganization of cell architecture and kinetochore (KT) composition with the exquisite phosphorylation of mitotic regulators, to ensure timely and temporal prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…This idea was corroborated by the analysis of the electrophoretic running properties of Astrin in lysates obtained from cells arrested in mitosis by different treatments (Figure 2A). Confirming previous reports, Astrin was strongly upshifted, indicative of phosphorylation, in nocodazole arrested mitotic cells when compared to thymidine-arrested, interphase cells (Chung et al, 2016). This upshift was further enhanced by arresting cells in STLC, mimicking conditions under which Plk1 and Astrin co-localise at the kinetochore ( Figure 1A).…”
Section: Plk1 Phosphorylates the N-terminus Of Astrinsupporting
confidence: 91%
See 1 more Smart Citation
“…This idea was corroborated by the analysis of the electrophoretic running properties of Astrin in lysates obtained from cells arrested in mitosis by different treatments (Figure 2A). Confirming previous reports, Astrin was strongly upshifted, indicative of phosphorylation, in nocodazole arrested mitotic cells when compared to thymidine-arrested, interphase cells (Chung et al, 2016). This upshift was further enhanced by arresting cells in STLC, mimicking conditions under which Plk1 and Astrin co-localise at the kinetochore ( Figure 1A).…”
Section: Plk1 Phosphorylates the N-terminus Of Astrinsupporting
confidence: 91%
“…In Plk1 immunoprecipitations, both Astrin and Kinastrin were co-precipitated ( Figure S1A). Interestingly, Plk1 only precipitated the slower migrating, mitotically phosphorylated form of Astrin (Chung et al, 2016), suggesting that the interaction between Plk1 and the Astrin complex is phosphorylation-dependent. Plk1 is known to bind to interaction partners via its Cterminal polo-box domain (PBD) to phosphorylated docking sites containing the motif S-pS/pT-P/X ( Figure 1C) (Elia et al, 2003a;Elia et al, 2003b).…”
Section: Plk1 Associates With the N-terminus Of Astrinmentioning
confidence: 99%
“…It was shown that SPAG5 inhibits or activates Separase depending on its status of phosphorylation 41 , 42 . As the phosphorylation status of SPAG5 was shown to be controlled by PLK1 44 , our data suggest that the CDC20B/PLK1/SPAG5 complex could control the timing of Separase activation locally in deuterosomes. It is therefore possible that multiple modes of activation of Separase may act in parallel to trigger the release of neo-synthesized centrioles in maturing MCCs.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, the phosphorylase cell division cycle (CDC) 14A dephosphorylates Astrin and negatively regulates Astrin localization on KT ( Figure 1C ). This indicates that the dynamic kinetochore localization of Astrin is also regulated by mitotic kinases ( Chung et al, 2016 ).…”
Section: The Dynamic Localization Of Astrin In Mitosismentioning
confidence: 99%